Self-Punch Lines as Successful Jokes : Analyzing The Stand-Up Comedy Performance of Jimmy O Young - Cut Nina Sausina (ESENSI LINGUA, 2022)
Humour is supposed to create hilarity or amusement either in conversation or in a comedy show. Some strategies are needed to deliver successful jokes. This research intends to recommend sequential organization as a strategy in doing stand-up comedy by analyzing a video that showed Jimmy O Young solo performance, a Chinese descent who has American citizenship. By using qualitative method this research is intended to answer two research questions. The first is which sequential organization proposed by Scarpetta & Spagnolli (2009) do fit Jimmy O Young stand up performance. And the second is how does he perform them in his stand-up performance. The results shows that Jimmy O Young fits all sequential organizations proposed by Scarpetta & Spagnolli (2009), and he performs his show very successfully by using informal registers, use his family and personal life experiencies as topic jokes, and always refers punchline to himself, rather than referring to the audience.